People's Voice Survey-India Country Brief 2023 - PHFI; QuEST (Quest Network, 2023)
People's Voice Survey (PVS) is a new instrument that measures health system performance from the population's perspective. It assesses the use of health care as well as people’s experiences, expectations, and confidence in the health system
Keywords: Health parameters; Health Indicators